Tolerability and safety of galcanezumab in patients with chronic cluster headache with up to 15 months of galcanezumab treatment. Issue 1 (22nd November 2021) - Láinez, Miguel J. A.; Schoenen, Jean; Stroud, Chad; Bardos, Jennifer; Bangs, Mark; Kemmer, Phebe; Wenzel, Richard; Kuruppu, Dulanji K.; Martinez, James Michael; Oakes, Tina M.
Abstract: Objective: The objective of the study was to assess the tolerability and safety of galcanezumab in patients with chronic cluster headache (CH) with up to 15 months of treatment. Background: Chronic CH is a highly debilitating disease with a substantial and unmet medical need. Methods: Patients were randomized to receive placebo or galcanezumab (300 mg) monthly for 12 weeks, followed by an optional 52‐week open‐label extension and 16‐week posttreatment follow‐up (washout). This is a secondary analysis and long‐term follow‐up of a previously conducted clinical trial. The safety analysis included patients who received galcanezumab at any time during the study. Outcomes included adverse events (AEs), discontinuations, laboratory values, vital signs, electrocardiograms (ECGs), and suicidality ratings. Results: A total of 233 patients received at least one galcanezumab dose. The mean exposure was 341 days. Galcanezumab‐treated patients were mostly male ( n  = 169/233; 72.5%) with a mean age of 44.9 (±10.9) years. Treatment‐emergent adverse events (TEAEs) were reported by 185 patients ( n  = 185/233; 79.4%), 23 patients ( n  = 23/233; 9.9%) reported serious adverse events (SAEs), and 18 patients ( n  = 18/233; 7.7%) discontinued due to AEs. The SAE CH was reported by three patients. The most common TEAEs (>10%) were nasopharyngitis ( n  = 41/233; 17.6%) and injection site pain ( n  = 33/233; 14.2%). 27.5% of patients ( n  = 64/233) had TEAEs related to injection sites. Likely hypersensitivity events, including injection site rash, injection site urticaria, and injection site hypersensitivity were reported ( n  = 14/233; 6.0%). There were past histories of suicidal ideation ( n  = 55/237; 23.2%) and suicidal behavior ( n  = 9/236; 3.8%). During the study, 15 patients ( n  = 15/230; 6.5%), seven with previous history, reported suicidal ideation. One patient had a nonfatal suicide attempt during the open‐label extension and an aborted attempt during the washout. There were no new safety findings compared with the placebo‐controlled treatment period in laboratory values, vital signs, or ECGs. Conclusions: Galcanezumab 300 mg monthly had a favorable tolerability and safety profile in patients with chronic CH with up to 15 months of treatment.